APPLICATION OF SMART WATER MONITORING SYSTEM IN ESTABLISHING CONTROL OF WATER CONSUMPTION IN IRRIGATION SYSTEMS - Sobirov Elmurod Rasul o’g’li; Ruzmetova Muxabbat Xujaniyazovna; Matyakubova Yulduz Omonboevna (International Journal of Innovations in Engineering Research and Technology, 2022)
In this article, one of the problems arising due to the increase in the population in modern times, in order to find a solution to the problems of water shortage for agriculture, it is stated that it is necessary to monitor the water flowing in the canals and achieve the correct distribution.